Teori Pertingkatan Norma dalam Usul Fikih - Anwar, Syamsul (UIN Sunan Kalijaga, 2016)
In this article, the writer investigates the possibility of the existence of the notion of legal norm hierarchy in IslamicLaw through analysing several key concepts such as hukm shar’i(detailed legal rule), asl kulli (general principle), qaidah fiqhiyyah (legal maxim), and kulliyyat (universals). The writer comes to the conclusion that itis possible to say the Islamic law knows the hirarchical structure of legal norms, but not in the formal sense of the term, rather much more in the substansial one. This means that every legal norm in Islamic Law is based on a higher norm, but this higher norm does notfunction as a norm which formally autorizes its making, but forms a source from which it can be drived.